How the IMF and World bank caused a resource curse and civil war in Mozambique - Joseph Hanlon (London School of Economics and Political Science (LSE), Department of International Development, 2022)
Mozambique's 3 rd civil war is now in its 5th year in Cabo Delgado province, in the northeast of the country. More than 4300 people have died and nearly one million people have been displaced, more than one third the population of the province. One of the largest investment projects in Africa has been halted by the war. President Filipe Nyusi blames unnamed foreign "evil forces". The United States blames Islamic State. But many researchers say the war is a local response to a resource curse - poverty and inequality have grown and local people are not benefitting from a promised natural resource "El Dorado". Only foreign companies and some members of the Mozambican elite appear to have gained. This, in turn, derived from "shock therapy" which was imposed on Mozambique at the end of the Cold War, with the goal of rapidly turning the "communist" elite into a capitalist elite. This created the local oligarchs who control access to the mineral and gas resources of Cabo Delgado, and do not share the wealth. Local people have now rebelled.
Keywords: 330; Mozambique; Cabo Delgado; gas; ruby; shock therapy; oligarch; inequality; corruption; World Bank; IMF; post-Cold War